Gerakan Sosial dan Hak Asasi Manusia dalam Masa Transisi Demokrasi di Indonesia - Kharisma Wardhatul Khusniah (Cendekia : Jurnal Hukum, Sosial dan Humaniora, 2024)
This article discusses how social movements can affect democratic transition in Indonesia and describes the impact of democratic transition on the development of human rights in Indonesia. The purpose of this article is to describe the relationship between social movements in the transition period of democracy and their relationship to the development of human rights. The discussion of this article shows that social movements and democratic transitions have a close relationship, where each other influences each other. A democratic transition would not have taken place if there had been no movement from civil society based on critical awareness. Social movements also encourage changes to a more democratic political system that guarantees respect, protection and fulfillment of human rights by the state. The democratic transition has a direct impact on the change and development of human rights. Among them is through the 1945 Constitutional Amendment which regulates guarantees for more comprehensive recognition and protection of human rights.